Solving the B-SAT Problem Using Quantum Computing: Smaller Is Sometimes Better - Bennakhi, Ahmad; Byrd, Gregory T.; Franzon, Paul (Entropy (Basel, Switzerland), 2024)
This paper aims to outline the effectiveness of modern universal gate quantum computers when utilizing different configurations to solve the B-SAT (Boolean satisfiability) problem. The quantum computing experiments were performed using Grover’s search algorithm to find a valid solution. The experiments were performed under different variations to demonstrate their effects on the results. Changing the number of shots, qubit mapping, and using a different quantum processor were all among the experimental variables. The study also branched into a dedicated experiment highlighting a peculiar behavior that IBM quantum processors exhibit when running circuits with a certain number of shots.